KONSEP DASAR PENGEMBANGAN KURIKULUM - Nur Isnaeni (Jurnal At-Tabayyun, 2023)
The curriculum is a tool used to achieve educational goals and provides guidance in implementing learning at all levels of education. The curriculum must be in line with the values of Pancasila and the 1945 Constitution which reflect the vision of a nation. A country's education system, from early childhood education to tertiary education, greatly influences the goals and patterns of life of that country. Changes in the government or education system can have an impact on changes in the applicable curriculum. As the main guideline, the curriculum has a strategic role in all educational activities. Therefore, curriculum preparation and development requires a strong understanding of the basic concepts of the curriculum. The national curriculum covers basic subjects with the aim of achieving the same competency standards throughout Indonesia, while curriculum development in each school is carried out specifically. Therefore, all parties involved in the world of education must have a deep understanding of the basic concepts of the curriculum, which are then used as a practical guide in implementing the curriculum at the school level.